The influence of adhesin protein from Aggregatibacter actinomycetemcomitans on IL-8 and MMP-8 titre in aggressive periodontitis - Rini Revijanti Ridwan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Adhesion can actually be considered as a part of both a powerful survival mechanism and a virulence mechanism for bacterial pathogens. Bacterial adhesin is an instrument for bacteria to do invasion to host. Bacterial adhesin depends on ligand interaction as a signaling mediator that will influence invasion and increase pro and anti-inflammatory because of the influence of the receptors of innate immune response. Aggregatibacter actimycetemcomitans has fimbriae included in type IV pili containing mostly with protein weighed 6.5 kDa and at least with protein weighed 54 kDa. Purpose: The purpose of this research is to analyze the influence of the induction of adhesin protein derived from A. actinomycetemcomitans on IL-8 and MMP-8 titre of Wistar rats. Methods: Adhesin protein derived from A. actinomycetemcomitans weighed 24 kDa was induced on the maxillary first molar sulcus of Wistar rats to prove that adhesin protein could affect IL-8 and MMP-8 titre. Next, to determine its influence, Elisa technique was conducted. Results: It is known that the levels of IL-8 and MMP-8 titre were increased in the group induced with adhesin protein derived from A. actinomycetemcomitans compared with the control group. Conclusion: It can be concluded that adhesin protein derived from A. actinomycetemcomitans can cause alveolar bone damage through the increasing levels of IL-8 and MMP-8 in aggressive periodontitis.